2012
DOI: 10.1007/s00535-012-0540-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lymph node metastasis in pancreatic neuroendocrine tumors (PNETs) based on the tumor size and hormonal production

Abstract: Non-gastrinomas with a tumor size of ≥15 mm and all gastrinomas would be an indication for pancreatectomy with lymph node dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…28 In the study by Tsutumi et al, the two patients with node-positive PNET of \10 mm were both gastrinomas. 7 Second, lymph node sampling was not performed in all of the patients. Parekh et al 27 examined the lymph node status of 149 patients who underwent surgical resection and showed that no lymph nodes were identified in the resected surgical specimens in 43 % of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 In the study by Tsutumi et al, the two patients with node-positive PNET of \10 mm were both gastrinomas. 7 Second, lymph node sampling was not performed in all of the patients. Parekh et al 27 examined the lymph node status of 149 patients who underwent surgical resection and showed that no lymph nodes were identified in the resected surgical specimens in 43 % of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies advocate surgical resection for PNETs of any size because even small tumors can be malignant or metastasize to lymph nodes. [2][3][4][5][6][7][8][9]27 Previous studies showing the incidence of lymph node metastases and/or prognosis according to tumor size were summarized in Table 3. Lymph node metastases were recognized even with PNETs of \10 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs have become reimbursable as antitumor drugs for treating advanced GI-NETs in Japan. Regarding NET, functionality, invasion depth, and the presence or absence of metastases must be correctly evaluated and treatment administered on the basis of the degrees of differentiation and malignancy of the tumor [4,[34][35][36]. Although surgical total excision is the standard treatment [37], some studies report that when radical treatment is difficult, debulking surgery of primary lesions and liver metastatic lesions effectively alleviate symptoms and improve prognosis [4,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…We elected to jointly analyze these because they are reliably available to a surgeon pre-operatively. Tsutsumi, K., et al, reported increase prevalence of lymph node metastasis in gastrinoma patients and non gastrinoma patients with tumor size ≥ 1.5 cm [26]. They also found that 2 (8%) patients with gastrinoma out of 26 patients with tumor < 1.5 cm had nodal metastasis [26].…”
Section: Discussionmentioning
confidence: 99%